2008
DOI: 10.1021/pr800383r
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis between the Domesticated Silkworm (Bombyx mori) Reared on Fresh Mulberry Leaves and on Artificial Diet

Abstract: To gain an insight into the effects of different diets on growth and development of the domesticated silkworm at protein level, we employed comparative proteomic approach to investigate the proteomic differences of midgut, hemolymph, fat body and posterior silk gland of the silkworms reared on fresh mulberry leaves and on artificial diet. Seventy-six differentially expressed proteins were identified by MALDI TOF/TOF MS, and among them, 41 proteins were up-regulated, and 35 proteins were downregulated. Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 47 publications
6
90
0
1
Order By: Relevance
“…One-dimensional sodium dodecyl sulfatepolyacrylamide electrophoresis (1D SDS-PAGE) were carried out according to (Zhou et al, 2008;Li et al, 2009) for haemolymph protein analysis, while the procedure established by Vasudha et al (2006) Qualitative analysis of proteins exhibited obvious variations in the number and position of bands between the larvae reared on each of the two investigated mulberry varieties. Most protein molecular weights were dominant in the two varieties except 91.23 and 72.92 kDa which appeared in M. alba var.…”
Section: Haemolymph and Silkgland Proteins Preparation And Analysismentioning
confidence: 99%
“…One-dimensional sodium dodecyl sulfatepolyacrylamide electrophoresis (1D SDS-PAGE) were carried out according to (Zhou et al, 2008;Li et al, 2009) for haemolymph protein analysis, while the procedure established by Vasudha et al (2006) Qualitative analysis of proteins exhibited obvious variations in the number and position of bands between the larvae reared on each of the two investigated mulberry varieties. Most protein molecular weights were dominant in the two varieties except 91.23 and 72.92 kDa which appeared in M. alba var.…”
Section: Haemolymph and Silkgland Proteins Preparation And Analysismentioning
confidence: 99%
“…Total protein extraction and quantification Each sample was homogenized in 200 ml of lysis buffer containing 8 M urea, 2 M thiourea, 4% (v/v) 3-[(3-Cholamidopropyl) dimethyl ammonio] propanesulfonate (CHAPS), 2% (v/v) immobilized pH gradient (IPG) buffer ( pH 3-10), and 0.1 M dithiothreitol for 10 min on ice and then kept for 10 min at room temperature, sonicated in an ice bath for 2 min, and centrifuged twice at 8000 g for 20 min at 188C [18]. The protein concentration in the supernatant was determined using BCA kit as described in manufacturer's instructions (SANGON, Shanghai, China).…”
Section: Spore Inoculationmentioning
confidence: 99%
“…Six belong to the short (S) subfamily . Comparative proteomic approach identified that PGRP was up-regulated when reared on fresh mulberry leaves when compared with on artificial diet (Zhou et al, 2008). B. mori GNBP was found to constitutively express in fat body and rapidly induced following a cuticular or hemoceolien bacterial challenge (Lee et al, 1996).…”
Section: Intmentioning
confidence: 99%